Use digital classification to follow change detection of al Razzazah sebkha For the period(1976-2013) (Journal of the College of Education for Women, 2019)
The Sebkha is considered the evaporative geomorphological features, where climate plays an active role. It forms part of the surface features in Mesopotamia plain of Iraqi, which is the most fertile lands, and because of complimentary natural and human factors turned most of the arable land to the territory of Sebkha lands. The use satellite image (Raw Data), Landsat 30M Mss for the year 1976 Landsat 7 ETM, and the Landsat 8 for year 2013 (LDCM) for the summer Landsat Data Continuity Mission and perform geometric correction, enhancements, and Subset image And a visual analysis Space visuals based on the analysis of spectral fingerprints earth's This study has shown that the best in the discrimination of Sebkha Remote sensing techniques and Geographic information system(GIS) proved the efficiency in determining the spatial distribution of the crust of salt sebkha and arable soil moisture content by different visual interpretation and digital advanced classification (statistical), Then the expense of space, time and conduct analysis and matching process conducted between the years of study in geographic information systems program after the application of water guide NDWI using a statistical formula To isolate the Pixels to extract water only own, to determine the change in the water area during the period of study todemonstrate the impact on the spread of salt Sebkha Besides the salinity and poor amount water surface and slow flow, climatic conditions suitable for the occurrence of the area under investigation, within the dry and semi-dry climate, which is characterized by high temperatures and lack of rainfall that cause increased evaporation from water bodies and in low land areas, In addition to the role of human factors of agricultural, industrial and urban activities. And analysis of the positive and negative of basic elements and heavy elements of surface and ground water was performed, besides the soil with regard.